My name is Asher Lev - Potok, Chaim (New York : Fawcett Crest, 1983)
The novelist records the anguish and triumphs of a young painter as he emerges into the great world of art and rejects all else.
Keywords: Jews -- New York (State) -- New York -- Fiction; Crown Heights (New York, N.Y.) -- Fiction; Jewish families -- Fiction; Young men -- Fiction; Artists -- Fiction